Oligodendroglia/MCT1 are an unexpected contributor to CNS toxicity/neurodegeneration - Rothstein, Jeffrey D. (Henry Stewart Talks, 2013)
The variety of cellular pathways causing Amyotrophic Lateral Sclerosis (ALS), A new ALS-causing cellular pathway implicating oligodendroglia and their newly discovered property of metabolic support neurons via lactate transport, Unexpected major cellular injury in ALS gray matter and the relationship to newly discovered ALS-causing pathway – Current and future targets for therapeutic intervention in ALS